2020
DOI: 10.3390/molecules25173911
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Processing of a Functional Beverage Containing Apple Juice and Aqueous Extract of Pfaffia glomerata Roots: Fructooligosaccharides Chemical Stability after Non-Thermal and Thermal Treatments

Abstract: The effects of supercritical CO2 processing on the chemical stability of fructooligosaccharides (FOS) and other functional and nutritional compounds were evaluated employing non-thermal and thermal approaches. Apple juice was enriched with Pfaffia glomerata roots aqueous extract due to its high content of short-chain FOS and then subjected to different levels of temperature (40 and 60 °C), pressure (8 and 21 MPa), and CO2 volume ratio (20 and 50%). The percentage of CO2 volume was evaluated concerning the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
(48 reference statements)
2
20
0
Order By: Relevance
“…® , São Bernardo do Campo, Brazil), cooled at −6 °C using a thermostatic bath (Marconi ® , model MA-184, Piracicaba, Brazil) and pressurized by using a pneumatic pump (Maximator ® , model M-111 L, Nordhausen, Germany), was pumped to the high-pressure reactor, promoting the homogenization of the sample until the operating pressure was reached. All experiments were carried out with a CO 2 volume ratio of 50% and a processing time of 10 min, according to previous works [ 22 , 27 , 28 ]. The processing time was counted only when the system reached the operating temperature and pressure according to each experimental condition studied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…® , São Bernardo do Campo, Brazil), cooled at −6 °C using a thermostatic bath (Marconi ® , model MA-184, Piracicaba, Brazil) and pressurized by using a pneumatic pump (Maximator ® , model M-111 L, Nordhausen, Germany), was pumped to the high-pressure reactor, promoting the homogenization of the sample until the operating pressure was reached. All experiments were carried out with a CO 2 volume ratio of 50% and a processing time of 10 min, according to previous works [ 22 , 27 , 28 ]. The processing time was counted only when the system reached the operating temperature and pressure according to each experimental condition studied.…”
Section: Methodsmentioning
confidence: 99%
“…However, the conventional thermal treatments currently used to stabilize fruit-based beverages can promote losses in their nutritional and bioactive properties due to the degradation of thermosensitive compounds (e.g., vitamins, ascorbic acid, phenolic compounds, antioxidants, proteins, and carbohydrates, among others). This can reduce their sensory quality through the formation of off-flavors, a “cooked taste”, and non-enzymatic browning [ 18 , 22 ]. Thus, one of the greatest challenges facing the food industry today is the development of technologies that ensure the safety of food products while preserving their sensory, nutritional, and functional attributes, similar to those of unprocessed products [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the biorefining approach to enhance the cannabis SFE extracts by integrating innovative green technologies, supercritical CO 2 -based manufacturing processes have been highlighted due to the slight impact of their application on different macronutrients, such as proteins, sugars, starches, dietary fibers, and others [98][99][100][101][102]. Cannabis sativa L. exhibits many industrial properties for application in different sectors depending on its plant fraction.…”
Section: Non-thermal Supercritical Co 2 Processing Of Cannabis Biomassmentioning
confidence: 99%
“…The key point that makes CO 2 an attractive solvent for food intents is the fact that it is a substance that is not chemically reactive [111]. Indeed, many studies reported the chemical stability of macronutrients after supercritical CO 2 processing such as sugars [99,102], dietary fibers [100], proteins [112,113], and others.…”
Section: Non-thermal Supercritical Co 2 Processing Of Cannabis Biomassmentioning
confidence: 99%
“…Supercritical CO 2 can be used for removing ethanol from aqueous solutions and therefore has been proposed for developing a low-alcohol beverage from wine, maintaining the aroma and the antioxidant activity similar to that of the original wine [158]. The same technique has been also used for the stabilization of FOS-rich beverages, maintaining the prebiotic functionality [159].…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%